Kembali ke fitrah dalam puisi-puisi Suhaimi Haji Muhammad - Abd Rahman, Samsina (Penerbit Universiti Kebangsaan Malaysia, 2013)
Human beings in their life always need to be reminded and advised not to forget their responsibilities and duties as Allah’s servant and His Caliph. They are always required to purity themselves from sins and deviant behavior by returning to their nature. They are also reminded about Allah’s promise in relation to the rewards of Heaven or Hell in the here afterwards that all depends on their deeds while living in this world. Hence a prolific poet, Suhaimi Hj. Muhammad is using his poems as an instrument to encourage people to do good things and avoid bad behavior. His collective work entitled at-Tariq (2002), an-Nur (2003), Asyik (2006), as-Salam (2006) and Taman Takwa (2009) contain advice, reminders encouraging people to create good personality and carry out their responsibilities. In other words, human beings need to be, knowledgeable, have a good personality, need to preach and learn form history to achieve their holy nature in understanding themselves and knowing their final destiny. All collective work of Suhaimi Hj. Muhammad are analysed by using the SPB4L theory proposed by Mohd. Yusof Hasan. The findings show that all principles of thought SPB4L are found in his work.